Impacts of the El Niño-Southern Oscillation (ENSO) on paddy production in Southeast Asia - Ismail, Normaz Wana; Seen, Mun Chan (Taylor and Francis, 2020)
Stronger intensity and frequent arrival of the El Niño- Southern Oscillation (ENSO) caused varied temperature and wildly varying precipitation with drought and flood conditions that threaten paddy production. Using the Pooled Mean Group estimation method, this study investigates the long run and short run relationship of ENSO impact on Southeast Asia paddy production from 1961 to 2014 with Oceanic Niño Index, Niño 3.4 sea surface temperature anomalies, Southern Oscillation Index and Multivariate ENSO Index. This study also investigates four different ENSO intensities with Multivariate ENSO Index to determine their long run and short run impact on paddy production. The findings reveal that the ENSO effect is exclusively captured by Multivariate ENSO Index among four climate change variables. Furthermore, ENSO arrival during the paddy planting season caused a paddy reduction in the long run. Specifically, the arrival of a moderate La Niña during the paddy planting season has a greater impact on paddy reduction in the long run compared to a strong El Niño. In addition, moderate and strong La Niña caused higher paddy production in the short run. Further research can be carried out by including spatial and temporal ENSO impacts on paddy planting season with single cultivation method.